Can worry and physiological anxiety uniquely predict children and adolescents' academic achievement and intelligence?. Issue 1 (2nd January 2021) - Castagna, Peter J.; Calamia, Matthew; Davis III, Thompson E.
Abstract: When exploring the relationship anxiety has with IQ, academic achievement studies often rely on diagnostic groups or total scores for an anxiety measure. The differential effects caused by anxiety dimensions, as well as their interactions, were examined with an exploratory method. This study examined the main effect of worry and physiological anxiety as predictors of youths' academic and cognitive functioning. Two samples of youth that presented to an out-patient clinic ( n = 121, M = 10.59, SD = 2.78, range = 6–16; n = 92, M = 10.07, SD = 2.76, range = 6–16) were administered well-established performance measures of academic and intellectual functioning, along with a measurement of anxiety. In an exploratory analysis, the interaction between worry and physiological anxiety was the only significant effect, robust across all academic composites and intelligence indices. Physiological anxiety had a differential relationship with academic achievement domains (and processing speed) dependent on levels of worry; low-levels of worry were predictive of improved scores at high, but not low-, levels of physiological anxiety. In contrast, high-, but not low-, levels of physiological anxiety were associated with lower scores when accompanied by elevated levels of worry when predicting intelligence indices.